THE INFLUENCE OF UNDERSTANDING THE TRI-NGA AND NATIONALISM ON INTEREST IN A CAREER IN TAXATION - Wardani, Dewi Kusuma; Pratiwi, Anggil (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
This study aims to determine the effect of understanding the tri-family, nationalism on career interest in the tax field. This research is Quantitative in nature using primary data taken through google questionnaires as many as 116 respondents were selected in this study using snowball sampling technique. This research was processed using IBM SPSS 22.0. The results of this study indicate that understanding the tri-group has a significant effect on career interest in taxation and nationalism has no significant effect on career interest in taxation.